Religious Policy Of The Soviet Union And Islam (On The Example Of Central Asia) - Kadyrov, Mederbek; Zuuridinov, Öskönbay (Scientific Journal of Faculty of Theology, 2019)
During the Soviet Union, atheism was the main ideology of the state. On the one hand, the Soviet administration propagated atheism on the one hand and fought against religious institutions and formations. Occasionally, it has changed religious policy. This article examines the religious policy of the Soviet Government and the general situation of the Islamic religion in that geography.